(untitled) (Bangladesh Journal of Medical Science, 2024)
Few studies have examined the performance of recalling Arabic letters. Some studies suggest that the low recall performance of Arabic letters may be attributed to the inherent visual complexity of Arabic script, while others highlight poor visual attention abilities among Arabic readers. In this context, the present study focuses on investigating immediate memory and the factors influencing its capacity among young Arabic readers. Immediate memory refers to the number of letters an observer can recall in a free recall task. Three experiments were conducted to examine the effects of exposure time (50, 100, and 200 ms), letter spacing (0.04°, 0.36°, and 1°), and stimulus type (acquired vs. non-acquired). Acquired stimuli consisted of Arabic and Latin letters, whereas non-acquired stimuli included Amazigh letters. It is noteworthy that our participants had no prior exposure to the Amazigh language. The results revealed significant effects of exposure time, letter spacing, and stimulus type on performance in the free recall task. In light of these findings, the study provides a discussion of factors that may account for the low recall performance observed in previous research. Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 834-845